(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background. Childhood cataract is an important cause of blindness in children and imposes a huge socio economic burden on society. Purpose. Aim of the study is to identify the visual outcome after cataract surgery in paediatric age group and to study the various factors which influence visual outcome and surgical complications in paediatric cataract surgery. Material and Methods. This prospective study conducted at a tertiary Eye care Hospital for the period of September 2016 to February 2017. 30 children who presented with developmental cataract or congenital cataract in the age group of 2months – 16 years included in this study. Visual acuity in children less than 5 years was assessed using picture chart, E charts and Cardiff acuity cards and by snellen’s chart for >5 years age children. Biomicroscopy, Fundus examination, and A scan were done. Children were reviewed every day for first day and then every week for first month and every 3 months for the first year after cataract surgery. Results. There were males (56.67%) dominance. Visual Inattentiveness/ defective vision was observed in 29(64.4%) of eyes. 13(33%) children had consanguity. Most of them were bilateral 26 (87%). Nystagmus was found to be the most common6 (20%) associated ocular anomaly. Vision at the time of presentation was less than 6/60 in better eye in 30 eyes (66.66%). Commonest type of cataract was total cataract 20(44.44%), followed by lamellar cataract 10 (22.22%). 45 eyes were operated, and IOL was implanted 73.33% of the eyes. Posterior capsulotomy with or without anterior vitrectomy was done in children less than 8 years of age. Following retinoscopic refraction, children were prescribed bifocal spectacles. Aphakic spectacles were prescribed in needed cases. Visual outcome at the end of 6 weeks was found to be greater than 6/24 in 66.66%. At the end of 12 months, vision greater than 6/24 was 48.88%. Posterior Capsule Opacification (PCO) was thick enough to require capsulotomy in 4 eyes. 3 Children underwent YAG capsulotomy. 1 eye needed surgical membranectomy. Complications other than PCO that was noted in this study were amblyopia which was seen in 5 eyes and optic capture in 2 eyes, anterior synaechiae in 1 eye and vitreous haemorrhage in 1 eye. Conclusion. Children less than 8 years who underwent primary posterior capsulotomy with or without anterior vitrectomy showed good visual outcome. PCO is the commonest complication and a major cause for visual obscuration following surgery, though the incidence of PCO has been brought down with modified surgical techniques and newer IOL designs. Children who underwent YAG/surgical capsulotomy had significant visual gain. Children with amblyopia who had strict adherence to occlusion therapy had significant improvement in visual acuity.